Mikrorastiščne razmere kot pomemben dejavnik uspešnosti premene smrekovih monokultur na bukovih rastiščih na Pohorju - Vilhar, Urša (Gozdarski vestnik, 2016)
In Slovenia as well as in Central Europe, large areas of Norway spruce monocultures were established on sites of different forest communities. This resulted in 6 to 7 million hectares of pure Norway spruce stands outside its natural areal, whereas in Slovenia there is currently around 30% of forests with antropogenically altered tree composition. In recent years, soil degradation, repeated droughts and bark beetle attacks were the main reason for the increased mortality of trees in spruce monocultures, establihed on originally deciduous sites. Scenarios of climate change show that growing conditions for Norway spruce in most cases might get worse due to global warming. Results of this study demonstrate that soil properties and ground vegetation have changed due to establishement of Norway spruce monocultures on Pohorje, which might affect the success of reintroduction of broadleaf species. In addition, microclimate, soil properties and ground vegetation in fenced spruce stand whith underplanted beech samplings are adressed. Organic matter decomposition is slowest in a closed spruce stand and fastest in a fenced spruce stand with underplanted beech samplings, especially on its forest edge and in the gaps. The highest plant species diversity was found in mixed spruce and beech stand and lowest in beech stand, followed by spruce stand. We found no difference in microclimate between fenced spruce stand and gap with underplanted beech samplings. However, lowest soil water content and highest drought stress was found on the forest edge, where the competition of plants for available water in the soil is maximal. Soil properties and plant species diversity of selected stands on Pohorje indicate more favorable conditions for reintroduction of broadleaf species compared to some other Norway spruce forests in Europe.
Keywords: smreka; premena; podsadnja bukve; talne razmere; rastlinska vrstna pestrost; microclimate; mikroklima; sušni stres